Promoting women's health in remote Aboriginal settings: Midwifery students' insights for practice - Thackrah, Rosalie; Thompson, S.; Durey, A. (2015)
Objective: To describe midwifery students' insights on promoting health to Aboriginal women in remote Australia following a supervised clinical placement. Design: Semistructured, in-depth interviews were conducted with all midwifery students who undertook the placement between 2010 and 2013. Setting: Aboriginal communities on the Ngaanyatjarra Lands, Western Australia. Participants: Undergraduate and postgraduate midwifery students from a Western Australian university. Interventions: Remote cultural immersion clinical placement. Main outcome measures: Student learning related to culturally respectful health care delivery and promotion of health.